Pengembangan Media Pembelajaran Trainer Conveyor Menggunakan Siemens S7-1200 pada Mata kuliah Praktik Sistem Kendali Industri - Aditya Rahman; Muhammad Fatkhurrokhman; Endi Permata (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
The rapid advancement of industrial automation requires vocational education institutions to provide laboratory facilities relevant to modern manufacturing needs. However, practical learning in Industrial Control Systems courses within the Vocational Electrical Engineering Education study program currently remains abstract due to the absence of real physical conveyor components. This study aims to develop a learning medium in the form of an item-sorting conveyor trainer based on the Siemens S7-1200 PLC, integrated with structured jobsheets. The research method employed is Research and Development (R&D) using the Four-D (4D) development model. The feasibility of the medium was evaluated through instrument validation, material expert validation, media expert validation, and student user-response trials. The results indicate that the conveyor trainer is highly feasible, achieving a material expert validation score of 85%, a media expert score of 83%, and a positive student response rate of 56.5%. The advantage of this device lies in its use of a global standard PLC and the integration of three distinct sensor types for object sorting. Consequently, this learning medium successfully bridges the gap between theory and practice, equipping students with direct practical skills aligned with the modern industrial ecosystem.